Defect engineering route to boron nitride quantum dots and edge-hydroxylated functionalization for bio-imaging. Issue 77 (3rd August 2016) - Jung, Jung-Hwan; Kotal, Moumita; Jang, Min-Ho; Lee, Junseok; Cho, Yong-Hoon; Kim, Won-Jong; Oh, Il-Kwon
Abstract : A defect engineering method was developed using physical energy sources to synthesize boron nitride quantum dots (BNQDs) for bioimaging applications. Abstract : Hexagonal boron nitride (h-BN) has considerable potential for applications owing to its attractive features including good thermal conductivity, chemical stability, and unique optical properties. However, because h-BN is chemically inert and thermally stable, it is hard to synthesize boron nitride quantum dots (BNQDs) using chemical methods such as oxidation, hetero-atom doping or functionalization. Here, we report a defect engineering method to synthesize BNQDs from h-BN using physical energy sources including an impinging process of heated iron nanoparticles, microwave irradiation and sonication. Furthermore, edge-hydroxylated functionalization was employed to enhance the intracellular uptake of the BNQDs in cells for bioimaging. The edge-hydroxylated BNQDs (EH-BNQDs) showed blue colored photoluminescence with 325 nm laser excitation, good cytotoxicity performance with approximately 100% cell viability, and a good attachment to cell surfaces. The successful endocytosis of EH-BNQDs using a cancer cell line was also demonstrated.